SOBRE A NATUREZA DO VERBO MONOARGUMENTAL NA ORDEM V NP - Coelho, Izete Lehmkuhl (Organon, 2012)
The aim of this paper is to examine quantitatively the V NP order inmonoargumental sentences of spoken Portuguese in Florianópolis. The analysisshows that the phenomenon of the NP V and V NP order does not constitute,properly, a case of variation, since types of verb (intransitive and unaccusative)and semantic roles of the NP (actor and theme) are bound to NP V and V NPorder, indicating their complementarity.